2013
DOI: 10.1002/ep.11877
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of activated carbon prepared from olive stones by microwave and conventional heating for iron (II), lead (II), and copper (II) removal from synthetic wastewater

Abstract: Activated carbon with high surface area was prepared from olive stone by microwave heating (MHOS) for the removal of a group of heavy metals Fe 21 , Pb 21, and Cu 21 from synthetic wastewater. As a comparison, activated carbon was also prepared by conventional heating (CHOS) method. The effects of different reaction parameters, such as adsorbent dosage, contact time, stirring speed, and initial pH, on pollutant removal efficiency were determined. The microwave heating requires significantly lesser holding time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…Loading the capsules was carried out by using 25 mg/L Co(II) solution at experimental conditions: initial pH 8.0, capsule amount: 10 g/L, contact time: 120 min, shaking speed 200 rpm, temperature: 25 AE 1 C. According to the Cytec Co., which produces Cyanex 272 [22], after liquid-liquid extraction of Co(II) with organic solvent Kermac 470B containing 12% Cyanex 272 as extractant and 10% p-nonylphenol as modifier, HCl solution can be used to strip Co(II) from loading organic phase. Moreover, Alslaibi et al [53] indicated that HCl solutions with different concentrations are efficient metal desorption solutions. They reported [52] that desorption of Fe 2+ , Pb 2+ and Cu 2+ from activated carbon prepared from olive stones by using microwave and conventional heating was found to be more effective by using 0.1 M HCl solution.…”
Section: Regeneration and Reusability Of Cyanex 272@psf Capsulesmentioning
confidence: 98%
See 2 more Smart Citations
“…Loading the capsules was carried out by using 25 mg/L Co(II) solution at experimental conditions: initial pH 8.0, capsule amount: 10 g/L, contact time: 120 min, shaking speed 200 rpm, temperature: 25 AE 1 C. According to the Cytec Co., which produces Cyanex 272 [22], after liquid-liquid extraction of Co(II) with organic solvent Kermac 470B containing 12% Cyanex 272 as extractant and 10% p-nonylphenol as modifier, HCl solution can be used to strip Co(II) from loading organic phase. Moreover, Alslaibi et al [53] indicated that HCl solutions with different concentrations are efficient metal desorption solutions. They reported [52] that desorption of Fe 2+ , Pb 2+ and Cu 2+ from activated carbon prepared from olive stones by using microwave and conventional heating was found to be more effective by using 0.1 M HCl solution.…”
Section: Regeneration and Reusability Of Cyanex 272@psf Capsulesmentioning
confidence: 98%
“…Therefore, in our study, we used 0.1 M HCl solution for desorption of Co(II) from loaded Cyanex 272@PSF capsules. It was found that desorption of Co(II) by using 0.1 M HCl solution was effective, which can be attributed to that the H + from HCl easily displaces Co(II) ions bonded to the capsules during the desorption process [53]. After desorption, Cyanex 272@PSF capsules were washed with distilled water untill neutralization and dried at room temperature.…”
Section: Regeneration and Reusability Of Cyanex 272@psf Capsulesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of agriculture byproducts such as coconut fruit (Anirudhan and Sreekumari 2011), nuts apricot (Tsibranska and Hristova 2010), beet pulp (Pehlivan et al 2008), stems of tea (Amarasinghe and Williams 2007), rice husk (Bakircioglu et al 2003;Wong et al 2003), pentandra hulls (Madhava-Raoa et al 2006)and olive stones-waste (Alslaibi et al 2015;Baccar et al 2009;Gharib and Ouederni 2005), which are inexpensive, abundantly available, and renewable materials, as precursor for activated carbon production, reduces adsorption processing costs (Bailey et al 1999). The adsorption process offers flexibility in design and operation and in many cases will produce high-quality treated effluent (Fu and Wang 2011;Cui et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Also the lignocellulose material can be used as adsorbent for the removal of pollutants from the wastewater either in its native form [2,3], treated form [4][5][6][7], or for production of active carbon [8,9]. Although there are several conventional treatments of wastewater, researchers are focused on the development of biotechnological solutions that are environmental friendly [10].…”
Section: Introductionmentioning
confidence: 99%